Building effective institutional frameworks to support pharmacogenetic research: an international empirical analysis. (13th January 2009) - Gaisser, Sibylle; Dreiling, Marieke; Hartig, Juliane; Hopkins, Michael M.; Ryan, Jim; Ibarreta, Dolores
As science unravels the genetic basis of disease, the opportunities offered by pharmacogenetics and pharmacogenomics (PGx) for future healthcare become more and more apparent. The objective of this paper is to analyse the current state of PGx research and explore future strategies for more efficient research projects and supportive infrastructures. Based on internet searches and an online survey of public research groups, the current focus of PGx technology and the institutional framework conditions for its performance were determined. The main areas of PGx research are the liver, neoplasms and the cardiovascular and central nervous systems. Collaborations are important for knowledge transfer between the private and public sectors. However, for strategic and confidentiality reasons, most collaborations are restricted to preclinical development, early stage clinical studies and the development of methods.